2020
DOI: 10.1177/1751143720954723
|View full text |Cite
|
Sign up to set email alerts
|

At the end: A vignette-based investigation of strategies for managing end-of-life decisions in the intensive care unit

Abstract: Background Decision-making on end-of-life is an inevitable, yet highly complex, aspect of intensive care decision-making. End-of-life decisions can be challenging both in terms of clinical judgement and social interaction with families, and these two processes often become intertwined. This is especially apparent at times when clinicians are required to seek the views of surrogate decision makers (i.e., family members) when considering palliative care. Methods Using a vignette-based interview methodology, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…through utilising JW liaison officers or chaplains). 26 While studies have reported that staff experience greater moral distress when patients are overtreated rather than undertreated, 27,28 being externally constrained from providing clinically indicated and routine lifesaving care might cause particular difficulty. To minimise the effect of staff distress, hospitals would do well to follow recommendations from the Guidelines for the Provision of Intensive Care Services, ensuring that a qualified psychologists are available to aid staff, patients, and their families.…”
Section: Discussionmentioning
confidence: 99%
“…through utilising JW liaison officers or chaplains). 26 While studies have reported that staff experience greater moral distress when patients are overtreated rather than undertreated, 27,28 being externally constrained from providing clinically indicated and routine lifesaving care might cause particular difficulty. To minimise the effect of staff distress, hospitals would do well to follow recommendations from the Guidelines for the Provision of Intensive Care Services, ensuring that a qualified psychologists are available to aid staff, patients, and their families.…”
Section: Discussionmentioning
confidence: 99%
“…These govern how we do right by our patient, but they might also lack the finesse required to incorporate religion, faith and conflict. The work by Reader et al reminds us of the need not to discount the overarching influence of spirituality and religion, 2 and we believe there is a need for us all to be more informed in this regard. Sometimes, these principles can even feel too Westernised and of less relevance to the relatives and loved ones of our patients.…”
mentioning
confidence: 99%
“…The recent qualitative study from Reader et al brings out several themes around end-of-life care in ICU that we believe have not yet been addressed sufficiently. 2 Whilst 'good communication' with families is often described as important, defining exactly what this involves is problematic, and getting these discussions right is an art that we all labour at for a lifetime.…”
mentioning
confidence: 99%